Sensitivity of weedy rice populations to Quizalofop - M. Oliveira Neto,Antonio (2020)
Abstract Background: Rice lines displaying resistance to quizalofop-p-ethyl (quizalofop), an acetyl coenzyme A carboxylase (ACCase)-inhibiting herbicide, were developed to facilitate control of imidazolinone-resistant weedy rice (red rice), as well as other susceptible grasses. Objective: To assess the sensitivity of weedy rice accessions from Brazil to quizalofop. Methods: Two bioassays were conducted on the greenhouse from March to June 2016, in a completely random design with a two-factor factorial combination of treatments and four replications. The factor A was weedy rice accession and factor B was quizalofop rates (0, 25 and 50 g a.i. ha-1). It was assessed a total of 84 genotypes in the two bioassays, composed of 78 weedy rice accessions, 4 rice cultivars, and 2 lines resistant to aryloxyphenoxypropionate (AOPP) herbicides. Quizalofop was applied the 2-leaf stage. Weedy rice control was evaluated at 28 and 22 days after treatment (DAT), respectively for bioassay I and II, using a scale of 0% (no control) to 100% (dead). Results: All weedy rice accessions were susceptible to quizalofop, being controlled 100% with 50 g a.i. ha-1. Rice lines SC 964 and SC 965, resistant to AOPP herbicides, were not injured by quizalofop. Conclusions: quizalofop is an effective tool for weedy rice control in ACCase-resistant rice.